Towards an analysis methodology for identifying root causes of poor delivery performance - Peter Nielsen; Ngoc Anh Dung Do; Thomas Eriksen; Izabela Nielsen (Foundations of Management, 2014)
This paper presents an analysis methodology for establishing the demand stability of the planning environment faced by a company and the impact on the stability from changes to sales order. The methodology focuses on three critical planning parameters derived from customer orders: product mix, volume, and order sizes. Furthermore, the methodology links the delivery performance of a company to the changes made to sales orders. Based on a test case application of the methodology, it is concluded that by accepting changes, the demand faced by the case company has become more unstable on product mix, volume, and the number of order lines per period, while some added stability has been achieved with regards to the order size distributions. Ultimately, by applying the methodology to the case company, it is found that by changing the sales orders, the company does not improve the delivery performance.
Keywords: 650; Business Intelligence; diagnostics; Decision Support Systems; Performance Improvement Systems